Expanding the clinical and genetic heterogeneity of SPAX5. Issue 4 (1st April 2020) - Dosi, Claudia; Galatolo, Daniele; Rubegni, Anna; Doccini, Stefano; Pasquariello, Rosa; Nesti, Claudia; Sicca, Federico; Barghigiani, Melissa; Battini, Roberta; Tessa, Alessandra; Santorelli, Filippo M.
Abstract: Mutations in the ATPase family 3‐like gene ( AFG3L2 ) have been linked to autosomal‐dominant spinocerebellar ataxia type 28 and autosomal recessive spastic ataxia‐neuropathy syndrome. Here, we describe the case of a child carrying bi‐allelic mutations in AFG3L2 and presenting with ictal paroxysmal episodes associated with neuroimaging suggestive of basal ganglia involvement. Studies in skin fibroblasts showed a significant reduction of AFG3L2 expression. The relatively mild clinical presentation and the benign course, in spite of severe neuroimaging features, distinguish this case from data reported in the literature, and therefore expand the spectrum of neurological and neuroradiological features associated with AFG3L2 mutations.